Pengaruh Environmental Social and Governance (ESG) Disclosure dan Sustainability Committe Terhadap Nilai Perusahaan - Fajar Sholachuddin; Sari Andayani (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure and the existence of a sustainability committee on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The population consists of all energy sector companies, with samples selected using purposive sampling based on specific criteria, resulting in 26 companies with a total of 78 observations. This research employs a quantitative approach using secondary data obtained from annual and sustainability reports. Data analysis is conducted using multiple linear regression with SPSS, along with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that ESG disclosure has a negative and significant effect on firm value, indicating that the market may perceive ESG practices as a cost burden or question their credibility. In contrast, the sustainability committee has a positive and significant effect on firm value, suggesting that stronger governance mechanisms enhance investor confidence and improve firm valuation. Simultaneously, both variables significantly influence firm value, although the model explains a limited proportion of variance. In conclusion, ESG disclosure alone is not sufficient to increase firm value without credible governance support, while the presence of a sustainability committee plays an important role in strengthening the effectiveness of sustainability practices and enhancing firm value.